Toward a Model of Organizational Mourning: The Case of Former Lehman Brothers Bankers - Crosina, Eliana; Pratt, Michael G. (Academy of Management Journal, 2019)
Focusing on the post-bankruptcy reactions of former Lehman Brothers’ bankers, we build a model of organizational mourning that depicts the thoughts, feelings, and actions of individual members dealing with the loss of their organization. We argue that organizational mourning is a process comprised of five interrelated phases, namely: (1) “experiencing the death event,” (2) “remembering the organization,” (3) “assessing loss,” (4) “salvaging: evaluate and restore,” and (5) “creating continuity and detaching.” Our empirical case suggests that at its core, organizational mourning involves both holding on and letting go of a defunct organization. Understanding how former members mourn is crucial to appreciate how they may ultimately find continuity after an organizational death, including how they enact their subsequent career paths. We conclude by discussing implications for theory of our research—notably, for literatures on post-death organizing, and personal mourning—as well as implications for practice.